2000
DOI: 10.1080/00332747.2000.11024929
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Two Years after the Oklahoma City Bombing in Youths Geographically Distant from the Explosion

Abstract: This article describes Posttraumatic Stress Disorder (PTSD) symptomatology in 69 sixth-grade youths who resided within 100 miles of Oklahoma City at the time of the 1995 bombing of the Alfred P. Murrah Federal Building. These youths neither had any direct physical exposure nor personally knew anyone killed or injured in the explosion. A survey conducted two years after the bombing assessed exposure, PTSD symptoms, and functioning. PTSD symptom frequency was measured with the Impact of Event Scale--Revised. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
147
2
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(166 citation statements)
references
References 0 publications
11
147
2
6
Order By: Relevance
“…10 Previous studies identified a number of factors in association with mental health status of people living in proximity to a disaster site, including severity of the disaster, level of exposure to the disaster, human and material loss to the family, perceived social support, adversity experienced by one's family members and/or acquaintance, personal links with someone living in the affected areas, whether one experienced the disaster in solitude, and one's proximity to the epicenter of the disasters. [11][12][13][14][15][16][17][18] In addition, viewing television images of disasters exacerbate PTSD and depression among persons directly affected by disasters. 19 Though no casualties or damaged buildings were reported in the downtown area of Chengdu, the capital city of the Sichuan Province, the city is only about 90 km away from the epicenter of the earthquake and is only 39 km away from Dujiangyan, where 3,091 deaths were reported.…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous studies identified a number of factors in association with mental health status of people living in proximity to a disaster site, including severity of the disaster, level of exposure to the disaster, human and material loss to the family, perceived social support, adversity experienced by one's family members and/or acquaintance, personal links with someone living in the affected areas, whether one experienced the disaster in solitude, and one's proximity to the epicenter of the disasters. [11][12][13][14][15][16][17][18] In addition, viewing television images of disasters exacerbate PTSD and depression among persons directly affected by disasters. 19 Though no casualties or damaged buildings were reported in the downtown area of Chengdu, the capital city of the Sichuan Province, the city is only about 90 km away from the epicenter of the earthquake and is only 39 km away from Dujiangyan, where 3,091 deaths were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Television coverage has also been implicated. [16][17][18][19][20] Combined forms of exposure may increase risk. For example, March and colleagues 11 found that posttraumatic stress symptomatology resulted from direct visual exposure and from indirect exposure through nonwitnessed harm to relatives and/or close friends in children 9 months after exposure to an industrial fire.…”
Section: Introductionmentioning
confidence: 99%
“…Mass media coverage of such events may expand their impact to youths not directly exposed (Pfefferbaum et al, 2000). National studies found that many adults (Silver, Holman, McIntosh, Poulin, & Gil-Rivas, 2002) and adolescents (Ford, Udry, Gleiter, & Chatala, 2003) reported event-related symptoms even 6-months later.…”
mentioning
confidence: 99%